Measuring adolescents' beliefs in conspiracy theories: Development and validation of the Adolescent Conspiracy Beliefs Questionnaire (ACBQ). (8th February 2021) - Jolley, Daniel; Douglas, Karen M.; Skipper, Yvonne; Thomas, Eleanor; Cookson, Darel
Abstract : Four studies (total n = 961) developed and validated the Adolescent Conspiracy Beliefs Questionnaire (ACBQ). Initial items were developed in collaboration with teachers. An exploratory factor analysis (Study 1, n = 208, aged 11–14) and a student focus group ( N = 3, aged 11) enabled us to establish the factor structure of a 9‐item scale. This was replicated via confirmatory factor analysis in Study 2 ( N = 178, aged 11–17), and the scale displayed good convergent (i.e., relationship with paranoia and mistrust) and discriminant validity (i.e., no relationship with extraversion). Study 3a ( N = 257) further tested convergent validity with a sample of 18‐year‐olds (i.e., relationship with adult‐validated measures of conspiracy beliefs) and demonstrated strong test–retest reliability. Study 3b ( N = 318) replicated these findings with a mixed‐age adult sample. The ACBQ will allow researchers to explore the psychological antecedents and consequences of conspiracy thinking in young populations.